The impact of country risk on nickel supply chain: based on complex network and panel regression analysis - Jia, Xiangying; Liu, Chonghao; Li, Tianjiao; Liu, Jing; Wang, Xiu (Frontiers in Earth Science, 2024)
Nickel is an important key resource and plays an increasingly important role in new energy technologies. The stability of its worldwide supply chain is crucial for addressing country risks and unforeseen events. To explore the impact of country risks on the stability of the global nickel supply chain, this study conducts a complex network analysis and panel regression analysis on nickel ore, ferro-nickel, and the stainless-steel trade data from 2000 to 2022. The study reveals the mechanisms by which economic and political risks affect the trade structure of nickel commodities and identifies the drivers of global nickel supply chain patterns. The study finds that an increase in economic risk promotes diversification of supply sources, while political risk hurts export scale and resource control ability. Industrial structure adjustments and R&D investments have a significant impact on trade structure, especially on the stainless-steel trade. China is a major consumer and importer, and occupies a central position in the global nickel trade network, while Indonesia and the Philippines’ policy changes have a significant impact on the market. This study provides an empirical basis for the risk management of the global nickel supply chain and a scientific basis for policy formulation and strategic planning.